2002
DOI: 10.1210/endo.143.3.8674
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Levels Increase Major Histocompatibility Complex Class I Gene Expression in Thyroid Cells and Amplify Interferon-γ Action

Abstract: Increased major histocompatibility complex (MHC) class I gene expression in target tissues may be relevant to the pathogenesis of autoimmune diseases. In this study, we questioned whether high glucose levels might increase MHC class I levels and thereby contribute to autoimmune complications. We used thyrocytes in continuous culture, because there is an increased incidence of autoimmune thyroiditis in type 2 diabetics and because transcriptional regulation of MHC class I is well studied in these cells. Norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The pSV0-CAT vector was obtained from the pSV2-CAT vector by removing the SV40 (Simian virus 40) early promoter sequences [17]. The reporter vectors were transiently transfected into the FRTL-5 cells using the diethylaminoethyl (DEAE)-dextran procedure [18,19]. The cells were grown to 60% confluency, maintained in 5H5% medium for 6 days, and then returned to 6H5% medium 12 h before transfection.…”
Section: Methodsmentioning
confidence: 99%
“…The pSV0-CAT vector was obtained from the pSV2-CAT vector by removing the SV40 (Simian virus 40) early promoter sequences [17]. The reporter vectors were transiently transfected into the FRTL-5 cells using the diethylaminoethyl (DEAE)-dextran procedure [18,19]. The cells were grown to 60% confluency, maintained in 5H5% medium for 6 days, and then returned to 6H5% medium 12 h before transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, cellular extracts from cells treated with compounds that cause an increase of MHC class I expression, as thymosin-a1 1 mg/mL or glucose 30 mM, showed a decrease of the silencer complex (Figure 3B 3). The choice of treatment conditions is based on our previous experiments (17,18,20) and are detailed in the Materials and Methods section. Figure 3D shows the effect of these treatments on the MHC class I RNA level, which confirm our previous studies Cell extracts from FRTL-5 cells maintained in 6H5% medium were then preincubated with antibodies against the p65 subunit of NF-kB and c-jun.…”
Section: Resultsmentioning
confidence: 99%
“…In more details, those studies have shown that some compounds such as TSH, MMI and C10 act inducing the formation of two protein-DNA complexes on a region that includes the constitutive 38 bp silencer of the MHC class-I promoter, which contains a CRE-like sequence (11,15). Other compounds as hydrocortisone, insulin/IGF-1, TGF-b1, thym and glucose act regulating the binding of the Mod-1 complex with the enhancer A element (12,(16)(17)(18)22). In most cases, an increase in Mod-1 binding stimulates the gene transcription, while a decrease inhibits it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations